Landscape Character: Relationship between existing Acts, Policies and Guidelines in Malaysia - Teh, Mohd Zulhaili; Ghani, Izham; Abdullah, Marina; Ahmad Pugi, Noorsazwan (Environment-Behaviour Proceedings Journal, 2020)
Landscape is an essential national resource which includes outstanding natural and cultural heritage. Landscape character assessment can make a valuable contribution to the formation of planning policies, to the allocation of land for development and development of control activities. Efforts in landscape development, preservation and conservation existed in this country indirectly through the introduction of various acts, policies and guidelines. Legislation on development protection and the direction is to provide landscape character assessment at national, regional and local levels through thorough and systematic ways in contributing to national development and an alternative to the protection, planning and landscape management. Keywords: Landscape character acts, policies and guidelines; Landscape character assessment. eISSN: 2398-4287Â© 2020. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer-review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: